MORPHOLOGY OF THE ADRENAL GLANDS OF GIANT ANTEATER (Myrmecophaga tridactyla, LINNAEUS, 1758) OF WILD LIFE - Santos, Amilton Cesar dos; Viana, Diego Carvalho; Leandro, Rafael Magdanelo; Rodrigues, Rosangela Felipe [UNESP]; Assis-Neto, Antonio Chaves de; Ferraz de Melo, Alan Peres [UNESP] (Univ Federal Uberlandia, 2016)
The Myrmecophaga tridactyla (family Pilosa), popularly known in Brazil as the giant anteater is classified as an endangered species by the main survey agencies of biodiversity preservation around the world. The adrenal glands are important organs, which are related to homeostasis of the animal. This study aimed to describe the morphology of the adrenal glands of M. tridactyla, providing data for future studies related to the production of steroid hormones in specimens exposed to different stress factors. The adrenal glands of 14 specimens were used. The glands were measured, photodocumented and described by light microscopy. The adrenals were positioned in the cranial extremity of the kidneys (left and right) and related medially to the caudal vena cava. The right adrenal gland had an elongated shape while the left adrenal gland had pyramidal or triangular shape. The weight was 4.765 +/- 0.129g for the right adrenal and 3.975 +/- 0.213g for the left adrenal. The length was 4.50 +/- 0.14cm for the right adrenal and 4.28 +/- 0.11cm for the left adrenal. The width was 2.60 +/- 0.13cm for the right adrenal and 2.37 +/- 0.12cm for the left adrenal. The thickness was 0.45 +/- 0.11cm for the right adrenal and 0.68 +/- 0.14cm for the left adrenal. Statistical differences (p<0.05) between right and left adrenals for all values analyzed were observed. Microscopically it was observed a capsule composed by modeled dense connective tissue lining the organ. Below this capsule, from the outermost to the innermost layer, it was observed a cortical region divided into glomerular, fasciculata and reticular zones with a medullar region occupying the center of the organ. Further studies related to steroidogenesis with specimens collected at different periods of the year are necessary, aiming to observe if there are morphological or hormonal variations in the adrenal glands due to seasonal periods. This information would be of great importance because it could reflect the behavioral habits of this species.
Keywords: Endangered species; Fasciculata zone; Glomerular zone; Reticular zone